Kinerja Kredit Usaha Rakyat Pada Perbankan Samarinda - Haryadi, Rina Masithoh (LPPM University 17 Agustus 1945 Samarinda, 2017)
This research to know the performance of people's business credit at one of retail bank at Samarinda in 2012 - 2014 which measured by Loan To Equity (LTE), Credit Risk Ratio (CRR) and Provission for Loan Losses (PLL). The result of Credit Risk Ratio (CRR) measurement in 2012-2013 shows that the credit performance of the people business has increased, which has a higher ratio which means unhealthy KUR performance in bank management capability to minimize the risk of bank credit failure. While the year 2014 has decreased that has a smaller ratio which means the performance of healthy KUR in the ability of bank management in minimizing the risk of bank credit failure.Measurement by using the Provision for Loan Losses (PLL) for 2012-2013, shows that the credit performance of the people business has increased that has a higher ratio which means that the bank's credit performance is not good the effectiveness of credit management many banks experiencing credit congestion. While the year 2013 until the year 2014 has decreased that has a smaller ratio which means the performance of good bank credit that is effectiveness management bank credit does not suffer a lot of credit congestion